Metagenomic Approach with the NetoVIR Enrichment Protocol Reveals Virus Diversity within Ethiopian Honey Bees (Apis mellifera simensis) - Haftom Gebremedhn; Ward Deboutte; Karel Schoonvaere; Peter Demaeght; Lina De Smet; Bezabeh Amssalu; Jelle Matthijnssens; Dirk C. de Graaf (Viruses, 2020)
Metagenomics studies have accelerated the discovery of novel or divergent viruses of the honey bee. However, most of these studies predominantly focused on RNA viruses, and many suffer from the relatively low abundance of viral nucleic acids in the samples (i.e., compared to that of the host). Here, we explored the virome of the Ethiopian honey bee, Apis mellifera simensis, using an unbiased metagenomic approach in which the next-generation sequencing step was preceded by an enrichment protocol for viral particles. Our study revealed five well-known bee viruses and 25 atypical virus species, most of which have never been found in A. mellifera before. The viruses belong to Iflaviridae, Dicistroviridae, Secoviridae, Partitiviridae, Parvoviridae, Potyviridae, and taxonomically unclassified families. Fifteen of these atypical viruses were most likely plant-specific, and the remaining ten were presumed to be insect-specific. Apis mellifera filamentous virus (AmFV) was found in one sampling site out of 10. Two samples contained high read counts of a virus similar to Diatraea saccharales densovirus (DsDNV), which is a virus that causes high mortality in the sugarcane borer. AmFV and the DsDNV-like virus were the only DNA viruses found. Three viruses that primarily infect Drosophila spp. were also discovered: La Jolla virus (LJV), Kilifi virus (KiV), and Thika virus. Our study suggests that phoretic varroa mites are involved in the transmission of LJV and KiV and that both viruses replicate in mites and adult bees. We also found an overwhelming dominance of the deformed wing virus type B variant, which fits well with the apparently harmless infestation by Varroa destructor. It was suggested that Ethiopian bees have developed tolerance against virus infections as the result of natural selection.